We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
151
3
avatar+874 

If f(x) = x^2 - 3x, then find f(-3).

 

Is it 0?
 

 Apr 21, 2019
 #1
avatar+104962 
+2

f(-3)  = (-3)^2  -3(-3)    =  9 + 9  =  18

 

 

cool  cool cool

 Apr 21, 2019
 #2
avatar+874 
+1

Thank you! I was debating between that answer! laugh

ant101  Apr 21, 2019
 #3
avatar+128 
-2

Substitute the variables.

 

f(-3) = -3^2 -(-9)

 

After that, simplify that...

 

f(-3) = 9+9 = 18

 

The answer is 18.

 

~~Hypotenuisance

 Apr 21, 2019

7 Online Users

avatar
avatar